2015
DOI: 10.1007/s13224-014-0607-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Oxytocin–Misoprostol Versus Oxytocin and Misoprostol Alone in Reducing Blood Loss at Cesarean Delivery: A Prospective Randomized Double-Blind Study

Abstract: About the Author AbstractPurpose To compare the effect of combined oxytocinmisoprostol versus oxytocin and misoprostol alone in reducing blood loss at cesarean delivery. Methods One hundred fifty patients of 18-40 years with singleton term pregnancies scheduled for cesarean section under spinal anesthesia were recruited in a prospective double-blind randomized clinical trial to one of the three following groups to receive 20 IU infusion of oxytocin (group O), 400-lg sublingual misoprostol tablets (group M) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Sublingual misoprostol is reported to have minimal adverse effects. 23 The decision regarding the dose of misoprostol was based upon the urgent need of fast and best effective dose at the threshold of 350 ml of blood loss. On reviewing the studies in context of dose, it was found that those reporting no additional benefit of misoprostol as an adjunct have used the dose of ≤600 µg.…”
Section: Discussionmentioning
confidence: 99%
“…Sublingual misoprostol is reported to have minimal adverse effects. 23 The decision regarding the dose of misoprostol was based upon the urgent need of fast and best effective dose at the threshold of 350 ml of blood loss. On reviewing the studies in context of dose, it was found that those reporting no additional benefit of misoprostol as an adjunct have used the dose of ≤600 µg.…”
Section: Discussionmentioning
confidence: 99%
“…Routine prophylactic use of uterotonic drugs, as combination of oxytocin with misoprostol, significantly lessens the risk of PPH. 25 Some studies show that oxytocin reduces PPH and the need for therapeutic uterotonic agents by over 40%, and that adding mysoprostol is more effective than using oxytocin alone. 26,27 Once the PPH is recognized, the conservative first line initial therapy is gaining uterine tonicity (up to 40 IU of oxytocin should be administered over 30 minutes), setting up a monitoring system and identifying the cause of bleeding (tone, tissue, trauma, and thrombin).…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be insufficient for prevention of postpartum hemorrhage (PPH), for example in patients who have hepatorenal disease, psychotic disorders, chronic anemia, allergy to melatonin, longterm antidepressant or analgesic drug use. Oxytocin may cause severe cardio-vascular complications, such as hypotension, due to vasodilation, especially in high doses (1). Melatonin, N-acetyl-5-methoxy tryptamine, is a methoxyindole derived from tryptophan and totally secrets by hypophysis.…”
Section: Introductionmentioning
confidence: 99%